THE HISTORICAL CUBA-U.S. DISCORDANCY FROM THE THEORETICAL OUTLOOK OF THE INTERNATIONAL RELATIONS - Seijos, Onesimo Julian Moreira (European Scientific Journal, ESJ, 2014)
This paper focuses on the main features of the relationship between Cuba and the United States (U.S.) since the nineteenth century to the present. The essay analyses the confrontation between these two countries from the theoretical view of International Relations (IR). The aim of the paper is to demonstrate that the nature of the Cuba-U.S. discrepancies during the Cold War is not confined to the ideological controversy of the East/West relations. Despite the changes that have taken place in world politics during the 1990s and the hopes which opened with the Obama administration, the design of U.S. policy towards Cuba has scarcely changed after the end of the Cold War. On the other hand, the revival of the Wilsonian ideas alleged in the mainstream IR literature does not take into account the special case of the Cuba-U.S relations. Regardless of the current trend to stress international institutions and to sort out conflict within the framework of international agreements, the Cuban problem remains as a national interest matter for the U.S. The historic sequence of the Cuban issue in American politics lend support to the argument that while within the academic discipline of International Relations there is a trend to consider the current period as a proof of the end of realism, the wires which lead the American political behaviour towards Cuba are still under the influence of old-fashioned national interest, the rational choice program and the U.S. dilemma of a superpower being challenged in its own hemisphere.